Influencing factors of diagnosis and treatment delay among rifampicin-resistant tuberculosis patients in Yunnan province, 2016 - 2021: a registration data analysis - Zichao LI; Yunbin YANG; Liangli LIU; Lin XU (Editorial Office of Chinese Journal of Public Health, 2024)
ObjectiveTo analyze the changes in the time intervals between diagnosis and treatment and the influencing factors of diagnosis and treatment delay among rifampicin-resistant tuberculosis (RR-TB) patients from 2016 to 2021 in Yunnan province, to provide a reference for reducing the occurrence of diagnosis and treatment delay in patients. MethodsData of 2 189 RR-TB patients registered in Yunnan province from 2016 to 2021 were extracted from the Tuberculosis Management Information System (TMIS) - a subsystem of the China Disease Prevention and Control Information System - to analyze the time intervals between symptom onset and diagnosis and that between diagnosis and treatment for the patients with different demographic and other characteristics. The time intervals were described in median and percentile 25th/75th (M, P25/P75) days, and multivariate binary logistic regression was used to analyze factors influencing delays in diagnosis and treatment of RR-TB patients. ResultsFor all patients, the median number of days from symptom onset to confirmed diagnosis of RR-TB increased from 50 in 2016 to 109 in 2018, but then decreased annually to 42 in 2021, with a trend of first increasing and then decreasing. The RR-TB patients who underwent conventional drug susceptibility testing and received initial diagnosis at a prefectural or municipal-level medical institution were more likely to have delayed diagnosis, with the odd ratio (OR) and 95% confidence interval (95%CI) of 5.193 (3.750 - 7.193) and 1.449 (1.199 - 1.752), respectively. The median number of days from diagnosis to treatment for the 1 488 RR-TB patients being treated increased slightly from one day in 2016 to 11 days in 2021. The RR-TB patients with the following characteristics were more likely to have treatment delays: being male (OR = 1.309, 95%CI: 1.063 - 1.612), being a farmer (OR = 1.317, 95%CI: 1.022 - 1.698), and being a permanent resident (OR = 4.016, 95%CI: 3.220 - 5.008) ; whereas RR-TB patients of younger age were less likely to have treatment delay, with the OR (95%CI) of 0.676 (0.487 - 0.938), 0.687 (0.494 - 0.954), and 0.663 (0.489 - 0.901) for the patients aged 25 - 34, 35 - 44, and 45 - 55 years respectively, compared with those aged ≥ 65 years. ConclusionDuring 2016 - 2021, the time interval between symptom onset and diagnosis was significantly shortened and the interval between diagnosis and treatment was relatively short for RR-TB patients in Yunnan province but attention still needs to be paid to patients at high risk of delayed diagnosis and treatment.